The Critical Period of Infancy from a Developmental Psychology Perspective: A Literature Review - Rahma Fithri; Yuliana Intan Lestari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The infancy period (0-2 years) is a critical phase in human development characterized by rapid growth and development across multiple domains, including physical-motor, cognitive, language, social-emotional, moral, and religious aspects. This period is often referred to as part of the